Crohn’s disease of the vulva in a 10-year-old girl - Kuloğlu, Zarife; Kansu, Aydan; Demirçeken, Fulya; Bozkir, Mehtap; Kundakçi, Nihal; Bingöl-Koloğlu, Meltem; Girgin, Nurten (The Turkish Journal of Pediatrics, 2008)
Crohn’s disease may involve all parts of the gastrointestinal tract and may often involve other organs as well. These non-intestinal affections are termed extraintestinal manifestations. Vulval involvement is an uncommon extraintestinal manifestation of Crohn’s disease, and it is very rare in children. Patients with vulval CD typically present with erythema and edema of the labia majora, which progresses to extensive ulcer formation. Vulval Crohn’s disease can appear before or after intestinal problems or it may occur simultaneously. We present a 10-year-old girl with intestinal Crohn’s disease complicated with perianal skin tags and asymptomatic unilateral labial hypertrophy. The course of her lesion was independent of the intestinal disease and responded significantly to medical treatment including azathioprine and topical steroid. We emphasize that although vulval involvement in childhood is uncommon, Crohn’s disease must be considered in the differential diagnosis of nontender, red, edematous lesions of the genital area.